2021
DOI: 10.1111/jonm.13347
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of actual turnover among nurses working in Korean hospitals: A nationwide longitudinal survey study

Abstract: Many countries are experiencing nursing shortages, which increases nurses' work demands (Kovner et al., 2014). In the United States (US), 80% of newly licensed registered nurses worked in hospitals, and they reported higher levels of turnover compared with experienced nurses (Kovner et al., 2016). The average tenure of Korean nurses is reported to be 5.4 years, with a 12.4% turnover rate (Hospital Nurses Association, 2019a).There are several issues confronting the nursing workforce in Korea. In 2016, the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
(31 reference statements)
0
27
1
Order By: Relevance
“…This underlying mechanism of turnover–outcome relationships was partially supported. The relationship between turnover and outcome can be explained by work conditions (Bae et al., 2021). High turnover can create poor work conditions that might be detrimental to the patient quality of care and their safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This underlying mechanism of turnover–outcome relationships was partially supported. The relationship between turnover and outcome can be explained by work conditions (Bae et al., 2021). High turnover can create poor work conditions that might be detrimental to the patient quality of care and their safety.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse turnover is costly and compromises quality of care and outcomes (Bae et al., 2021). As demonstrated earlier, previous studies have primarily investigated the factors contributing to turnover (Falatah & Salem, 2018; Halter et al., 2017; McDermid et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the low professional interest and engagement provoke the nurse turnover. The findings from the literature analysis show that nurse turnover provokes quality degradation and loss of efficiency in healthcare (Bae et al, 2021) causing an adverse economic impact (Halter et al, 2017). Having systemized the global scientific investigations on the economic impact of nurse turnover, Li & Jones (2013) found that the nursing turnover costs were from 0.31 to 1.3 times the average nurse salary.…”
Section: Economics and Businessmentioning
confidence: 99%
“…Based on a recent meta-analysis [ 2 ] on the extent of compassion satisfaction and fatigue and burnout, the rate of nurse burnout was reported to be 52%. Regionally, it was reported that the nurse burnout rate was highest in Southeast Asia including South Korea [ 3 ], and Korean nurses revealed higher levels of burnout through a nationwide survey [ 4 ], which was a predictor of actual turnover [ 5 ]. Burnout has a variety of negative impacts on both the personal and professional life of nurses, and furthermore, nurse burnout has been directly or indirectly associated with patient safety, quality of care, and patient satisfaction [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%